PENGARUH KESADARAN WAJIB PAJAK, PENGETAHUAN PERPAJAKAN, DAN SANKSI PAJAK TERHADAP KEPATUHAN WAJIB PAJAK BUMI DAN BANGUNAN PERDESAAN DAN PERKOTAAN DI PELEM, PRINGKUKU, PACITAN - Inaniatita, Erlisa; Tjahjono, Achmad (Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2023)
This study aims to examine the effect of taxpayers’ awareness, tax knowledge, and tax penalty on taxpayers’ compliance in paying rural and urban land and building tax in Pelem, Pringkuku, Pacitan. This research uses quantitative methods by performing multiple linear regression tests between the variables of taxpayer awareness, tax knowledge, and tax penalty on taxpayers’ compliance in paying rural and urban land and building tax. The sample in this study was determined by purposive sampling. This study concludes that the tax penalty variable has a significant positive effect on the compliance of the land and building taxpayers, while the taxpayer awareness and knowledge of taxation variables have no effect on the compliance of the land and building taxpayers. The adjusted R square value shows a value of 0.245, this identifies that all independent variables (taxpayer awareness, tax knowledge, and tax sanctions) are able to affect the dependent variable (taxpayer compliance) by 23.5%.